Statistical assessment of balancing real estate market - Kovtun N.; Shibirina S. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article was developed the system of statistical indicators of the real estate market. The balance of the real estate market was evaluated at the levels of its operation.